PEMBERDAYAAN IBU-IBU RUMAH TANGGA DALAM PEMBUATAN HANDSANITIZER LIDAH BUAYA (HANDSLIB) DI DESA PATALAGAN - Ulfah, Mariam; Irawan, Ade; Hadi, Ismanurrahman (Nindikayla Institute, 2023)
Patalagan is a village in Pancalang subdistrict, Kuningan. Almost all village residents work as farmers. The large potential of human resources is the main capital for this village to carry out empowerment activities, especially for housewives. One type of empowerment is making products that are very useful for supporting health and preventing disease, especially in this post-COVID era, namely hand sanitizers. This product can be made from simple chemicals. The composition can also be combined with herbal plants, for example Aloe vera which has various pharmacological activities, namely antibacterial, antifungal and antiviral. This plant is often found in Patalagan village, so it can be used to make aloe vera-based hand sanitizer (HANDSLIB). The aim of this service is to increase village residents' awareness of the health benefits of hand sanitizer and aloe vera and improve the skills of mothers in making hand sanitizer. The method used was education about the health benefits of handsanitizer and aloe vera for health and training in making HANDSLIB. The training activity was carried out on 04 February 2024 offline at the house of one of the residents of Patalagan village. Training and counseling was carried out with 12 participants. The results of the evaluation of hand sanitizer training activities showed that the mothers were skilled at making hand sanitizer made from aloe vera (Handslib)